The effective administrative protection in the administrative sanctioning procedure - Canosa, Armando N. (2020)
The purpose of this work is to stablish that the administrative sanctioning power is part of the administrative activity, therefore being away from judicial activity. As consequence of that, the sanctioning act will have the character of an administrative act and, therefore, to expedite the sanctioning act it will necessarily will transit an administrative procedure that will have essential guarantees. The most important, without doubt, will be the effective administrative protection that rules all kinds of administrative procedures, being the administrative sanctioning act a special of it. The studied guarantee contents principles that rule every administrative procedure that refer not only the individuals’ rights, but also the efficacy of administration acts.